Cultural Identity in Minoan Crete : Social Dynamics in the Neopalatial Period - Adams, Ellen (Cambridge University Press, 2017)
A comprehensive account of the Palaces, control networks and spatial dynamics of Neopalatial Crete, the floruit of the Minoan civilization